Effects of different inclusion levels of rice bran in the diets on the performance of African catfish (Clarias gariepinus) juveniles - Samuel, Deidre Eligius; Rossita Shapawi (Malaysian Society of Applied Biology, 2016)
A five-week feeding trial was conducted to evaluate the possibility of rice bran meal (RB) substituting dietary soybean meal (SBM) in the diet of African catfish, Clarias gariepinus juvenile. Five experimental diets were formulated with RB replacing 0 (RB0), 20 (RB20), 40 (RB40), 60 (RB60) and 80% (RB80) of SBM protein. Another two experimental diets with intermediate (40%) and maximum (80%) inclusion levels of RB were added with feed enzyme (Allzyme SSF) to investigate its effects in improving the feed utilization (RB40SSF and RB80SSF, respectively). The control diet (RB0) was formulated using fish meal and SBM as sources of dietary protein. All diets were isoproteic (30% protein), isolipidic (12% lipid) and isoenergetic (3.83kcal/g). There were no significant differences (P>0.05) in terms of weight gain (WG), specific growth rate (SGR), total feed intake (TFI), feed conversion ratio (FCR), survival rate (SR) and protein efficiency among all dietary treatments. Different inclusion levels of RB in diets did not affect the body indices of experimental fish. No definite trend was detected in whole body protein and lipid contents with increased dietary RB. It is concluded that RB can substitute SBM in the diet for C. gariepinus at up to 80% without significantly compromising growth and feed utilization. The addition of Allzyme SSF enzyme at 0.02g/100g diet has little contribution in improving growth and feed utilization performances.